SEJARAH PERADABAN DINASTI BANI UMAYYAH 661-750 M - Maulidan, Aldi Cahya; Rhamadan, Faishal Sahru (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This research discusses the history of the long journey of the Umayyad Dynasty. This research describes the process of establishment, development and progress, until the period of destruction of the Umayyad Dynasty. The Umayyad Dynasty was the first dynasty in Arabia that succeeded in expanding its territory, building its civilization, and spreading Islam throughout the world. This dynasty had an important role in the advancement of Islamic civilization. The Umayyad Dynasty succeeded in developing education, culture, military, government, economy, art, architecture and the extent of the territory that was successfully conquered. The methodology used in the historical research process of the Umayyad Dynasty is a content analysis approach. Content analysis is a research technique used to understand and analyze the content of documents or written materials, such as text, images, or audio. The results of the research provided information about the establishment of the Umayyad Dynasty. The Umayyad Dynasty's influential caliphs are described in the research results along with their policies, such as Mu'awiyah, Umar and Hisham. The success of the development and progress of Islamic civilization during the Umayyad Dynasty in various fields of life until its decline was also successfully revealed in this study.